Antimicrobial activity, phenolic compounds content, and antioxidant capacity of four edible macromycete fungi from Chihuahua, Mexico - Neida Aurora Martínez-Escobedo (Tip Revista Especializada en Ciencias Químico-Biológicas, 2021)
In the present study, antimicrobial activity, phenolic compounds content and antioxidant capacity of four edible fungi (Amanita rubescens, Astraeus hygrometricus, Laccaria laccata and Lycoperdon perlatum) were determined. Antimicrobial activities were tested against Staphylococcus aureus, Streptococcus agalactiae and Candida albicans. Phenolic compounds and antioxidant activity were measured by spectrophotometric methods. All mushrooms present high activity against S. agalactiae. Phenolics compounds content ranked between 1.54 - 20.93 mg GAE/g DW and the antioxidant activity ranked between 0.0034 – 0.0854 mmol TE/g DW being A. rubescens the specie with the highest values. The results obtained for the antimicrobial activity using the disc diffusion method indicated that the extracts exhibited moderated antimicrobial activity. However, the MIC results with both solvents show that all the macromycete species registered inhibition of the microorganisms in different concentration. Generally, the ethanol extracts exerted stronger antimicrobial activity than methanol extracts. Similarly, S. agalactiae was the most susceptible microorganism, followed by C. albicans. S. aureus was the bacteria most resistant. The best antimicrobial activity was found in the ethanolic extracts of A. hygrometricus and L. perlatum against S. agalactiae, with a MIC value of 3.75 mg/mL. In conclusion, it is suggested that these species can be used as a natural source of antimicrobial and antioxidant components.